Structural basis of the interaction between the putative adhesion-involved and iron-regulated FrpD and FrpC proteins of Neisseria meningitidis - Sviridova, Ekaterina; Rezacova, Pavlina; Bondar, Alexey; Veverka, Vaclav; Novak, Petr; Schenk, Gundolf; Svergun, Dmitri I; Kuta Smatanova, Ivana; Bumba, Ladislav (Scientific reports, 2017)
The iron-regulated protein FrpD from Neisseria meningitidis is an outer membrane lipoprotein that interacts with very high affinity (Kd ~ 0.2 nM) with the N-terminal domain of FrpC, a Type I-secreted protein from the Repeat in ToXin (RTX) protein family. In the presence of Ca2+, FrpC undergoes Ca2+ -dependent protein trans-splicing that includes an autocatalytic cleavage of the Asp414-Pro415 peptide bond and formation of an Asp414-Lys isopeptide bond. Here, we report the high-resolution structure of FrpD and describe the structure-function relationships underlying the interaction between FrpD and FrpC1-414. We identified FrpD residues involved in FrpC1-414 binding, which enabled localization of FrpD within the low-resolution SAXS model of the FrpD-FrpC1-414 complex. Moreover, the trans-splicing activity of FrpC resulted in covalent linkage of the FrpC1-414 fragment to plasma membrane proteins of epithelial cells in vitro, suggesting that formation of the FrpD-FrpC1-414 complex may be involved in the interaction of meningococci with the host cell surface.
Keywords: Bacterial Outer Membrane Proteins; membránové proteiny; periplazmatické vazebné proteiny; Iron-Binding Proteins; sekvence aminokyselin; Cell Adhesion; Membrane Proteins; proteiny vnější bakteriální membrány; Lipoproteins; X-Ray Diffraction; lipoproteiny; železo; proteiny vázající železo; Neisseria meningitidis; Bacterial Proteins; Iron; Humans; Amino Acid Sequence; buněčná adheze; Periplasmic Binding Proteins; bakteriální proteiny; difrakce rentgenového záření; lidé